Root Cause Analysis of Performance Degradation for an XYZ Thermal Power Plant in Tanzania - I. Marandu, Simon; Ally, Mkulungwa (Tanzania Journal of Engineering and Technology, 2025)
Thermal power plants in Tanzania have been experiencing performance degradation, typically arising from component and subsystem failures, which contribute to power system instability and unreliability. This paper presents a case study of the root causes of performance degradation of an XYZ thermal power plant. The study was conducted by reviewing plant documentations, including maintenance and operational data logbooks, and by standardising the approach through the adoption of ISO 14224:2016 for maintenance and reliability data exchange. Data evaluation was carried out using principal component analysis and scree plot analytical techniques to enhance the depth and accuracy of root cause identification. Additionally, Pareto analysis was employed to determine the extent of the degradation. The findings revealed that plant performance degradation was primarily caused by local environmental factors (i.e. dust and air salinity) and operational practices at the plant level, including skills gap and non-adherence to recommended maintenance schedules. With regard to component and subsystem failure incidents, the majority were valve and ignition system failures, accounting for 11.5% and 10.9%, respectively. The main failure modes were external utility fluid leakage (ELU) and overheating (OHE), which accounted for 23.32% and 18.78%, respectively. Moreover, instead of the 34,848 hours planned for proactive maintenance activities based on Original Equipment Manufacturer (OEM) recommendations, the plant consumed 127,392 hours, with over 80% dedicated to reactive maintenance. In conclusion, timely and proactive maintenance, supported by knowledgeable and skilled personnel, is crucial in ensuring stability, reliability, and longevity of the XYZ thermal power plant.